European coal geology - Whateley, M. K. G.; Spears, D. A. (Geological Society special publication, 1995)
Despite extensive closure of underground mines throughout the European Union, coal remains a major energy source and the growing energy demands of developing countries mean that the world's coal consumption continues to increase. The European Union has long-established coalfields and considerable research experience in coal exploitation and use, all of which will be important in the future development of coal. This volume covers many aspects of European coal geology and illustrates the depth and breadth of research from sedimentological, geochemical and exploration models, to exploration drilling and economic evaluation of coal deposits, on a local and country-wide scale, as well as the environmental aspects of coal burning and disposal of C02. The book will fill a gap in the literature on regional coal deposits, having encouraged papers in which description of such deposits is specifically orientated towards the application of the research in the exploration for, exploitation of and environmental considerations required in the study of coal. The well-balanced content of the book should provide a particularly attractive read for those who seek an update on some of the coal deposits of Europe. Such an extensive spectrum of papers will appeal to a wide audience, ranging from researchers, lecturers and students to professionals in industry.--Provided by publisher.